Thinking (too?) fast and slow: An example of professional judgement and decision making processes in athletics - Abraham, A.; Collins, D.; Collins, R. (International Journal of Sports Science and Coaching, 2025)
Recently there has been interest in using examining coaching practice through a lens of Professional Judgement and Decision Making. One core theory of decision making, Recognition Primed Decision Making, examines how people make decisions in limited time scales. Alternatively, when time allows, there is an opportunity for people to engage in slower thoughtful and Type 2 judgement and decision making (DM). In both cases it is hypothesised that professional practitioners (coaches) should draw on formalistic scientific rather than substantive heuristics or rules to maintain a professional standard. However, despite these ideas relatively little is known about the actual decision-making behaviour of coaches in practice. Against this premise 12 long jump coaches were asked to identify the strengths and weaknesses of a long jump athlete and offer a view on how they would work to improve his performance. All coaches were asked to identify what they would do if their first approach didn't work. Findings suggest that coaches have an initial tendency to engage in RPD type behaviour but drawing mainly on substantive rules. Notably, uncertainty pushed coaches to become more considered, and formalistic. In conclusion, coaches have the capacity to be `professional` in their DM behaviour but may not use this capacity as the first resort.